Effect of time to first shoot removal and the amount of shoots removed on the yield and quality of cassava leaves and tubers - Simwambana, M.; Ferguson, T.U.; Osiru, D.; Hahn, S.K. (1994)
The effect of time to first shoot removal and the amount of shoots removed on the yield and quality of cassava leaves and tubers were investigated in two experiments carried out at IITA, Nigeria using two cassava varieties, TMS 30572 and TMS 91934. Four different times to first shoot removal, 8, 14, 20, and 52 weeks after planting (WAP), i.e. SR8, SR14, SR20, and SR52, and five different amounts of shoot harvested: no shoot removed, tip only, tip and two fully developed leaves, tip and five fully developed leaves, and plucking the youngest leaves, excluding the apical shoot (SR1, SR2, SR3, SR4, and SR5), were imposed at 8 WAP and repeated after every 8 weeks for 52 weeks. The time to first shoot removal and the amount of shoots removed did not affect the tuber yield of the two cassava varieties. Detopping starting at 14 WAP (SR14) and repeated at an interval of 8 weeks gave the highest fresh shoot for vegetable. Plucking of a high proportion of older leaves (SR5) had a higher HCN concentration than the other shoot removal treatments. Leaf Ca concentration increased with an increase in proportion of fully developed leaves harvested while the crude protein and P concentrations decreased.